Safety evaluation of shorter infusion for ocrelizumab in a substudy of the Phase IIIb CHORDS trial. Issue 3 (23rd February 2021) - Bermel, Robert A.; Waubant, Emmanuelle; Pardo, Gabriel; Bass, Ann; Repovic, Pavle; Newsome, Scott; Lindsey, John W.; Kile, Deidre; Pradhan, Ashish; Musch, Bruno; Zabeti, Aram
Abstract: The CHORDS trial evaluated ocrelizumab (OCR) in patients with relapsing‐remitting multiple sclerosis who had a suboptimal response to previous disease‐modifying treatment. The objective of the present study was to assess the safety of shorter OCR infusions in a substudy of CHORDS. After completing four doses of OCR per initial US prescribing recommendations in the main study, participants in the substudy ( N = 129) received a fifth dose over a 2‐h duration (vs. 3.5 h). Infusion‐related reactions occurred in 12.4% of patients. None were severe, life‐threatening or led to treatment discontinuation. Shorter infusion time did not change the safety profile of OCR. Clinicaltrials.gov (NCT0237856).